An Interesting Case of Intramuscular Myxoma with Scapular Bone Lysis - Jérôme Tirefort; Frank C. Kolo; Alexandre Lädermann (Case Reports in Orthopedics)
Introduction. Intramuscular myxoma is a rare benign primitive tumor of the mesenchyme founded at the skeletal muscle level; it presents itself like an unpainful, slow-growing mass. Myxomas with bone lysis are even more rare; only 7 cases have been reported in the English literature, but never at the shoulder level. Case Presentation. We describe an 83-year-old patient with a growing mass in the deltoid muscle with unique scapular lysis, without any symptom. Magnetic resonance imaging (MRI) and a biopsy were performed and the diagnosis of intramuscular myxoma has been retained. In front of this diagnosis of nonmalignant lesion, the decision of a simple follow-up was taken. One year after this decision, the patient was still asymptomatic. Conclusion. In the presence of an intramuscular growing mass with associated bone lysis, intramuscular myxoma as well as malignant tumor should be evoked. MRI has to be part of the initial radiologic appraisal but biopsy is essential to confirm the diagnosis. By consensus, the standard treatment is surgical excision but conservative treatment with simple follow-up can be an option.